M. M. SPERANSKY’S CONTRIBUTION IN DEVELOPMENT OF LANGUAGE OF BUSINESS DOCUMENTATION IN THE LATE 18TH AND FIRST THIRD OF THE 19TH CENTURIES - Rumyantseva, Nataliya; Sapozhnikov, Pavel; Rubtsova, Dina (Revista Inclusiones, 2019)
In Russian science, it is generally accepted that Karamzin is a reformer of the Russian language, when heavy artificial forms alien to the Russian mentality or popular language were rejected and replaced with mobile, living forms. However, one person, even as famous and talented as N. M. Karamzin could not be the only language converter. Formation of the new forms of Russian literature, and enrichment of vocabulary of the emerging literary language were also facilitated by his predecessors such as, D. I. Fonvizin, N. I. Novikov, G. R. Derzhavin, A. A. Petrov and others. We consider it possible to include among them M.M. Speransky. The present paper proves that M. M. Speransky was the creator of Russian business communication